Crystallizer casting powder for high-manganese stainless steel continuous casting and application of crystallizer casting powder

A mold protection slag for high manganese stainless steel continuous casting, with specific chemical compositions, effectively absorbs Cr2O3 and other impurities, preventing black band formation and enhancing lubrication and heat transfer, thus improving the continuous casting process and reducing production costs.

CN119114881APending Publication Date: 2024-12-13XIXIA LONGCHENG METALLURGICAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411256594.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The issue of Cr-containing particles forming black bands on the surface of high manganese stainless steel billets during the rolling process, which affects appearance quality and increases production costs, is not effectively addressed by existing protective slags.

Method used

A mold protection slag for high manganese stainless steel continuous casting, composed of specific chemical components including CaO, SiO2, Cr2O3, MnO2, MgO, Al2O3, and F-, that reduces the melting point and viscosity, and incorporates Na and F- to improve lubrication and heat transfer effects, and the chemical stability, effectively absorbing Cr2O3 and other impurities to prevent black band formation.

Benefits of technology

The mold protection slag effectively absorbs and stabilizes the Cr-containing particles forming black bands on the surface of high manganese stainless steel billets during the rolling process, which enhances the lubrication and heat transfer effects, and the chemical stability, effectively absorbing Cr-containing particles forming high manganese stainless steel continuous casting process, which enhances the lubrication and heat transfer effects, and the chemical stability, effectively absorbing Cr-containing particles forming high manganese stainless steel continuous casting process, improving the quality of the ingot and reducing production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides crystallizer casting powder for continuous casting of high-manganese stainless steel and application of the crystallizer casting powder, and relates to the technical field of casting powder, and the crystallizer casting powder comprises the following chemical components in percentage by mass: 28-38% of CaO, 22-32% of SiO2, 0.5-1% of Cr2O3, 2.2-4.5% of MnO2, 1.5-5% of MgO, 2-7% of Al2O3, 3-9% of Na2O, 4-10% of F <-> and 3.5-6.0% of C. A proper amount of Cr2O3, Na < + > and F <-> enable the casting powder to keep activity and stability after absorbing high-melting-point oxides, so that the stainless steel has good lubrication and heat transfer effects in the continuous casting process, the continuous casting smoothness is improved, the casting blank quality is improved, the black belt quality problem caused by longitudinal cracks, edge cracks, inclusions and the like of a continuous casting blank is reduced, the product yield is improved, the casting blank grinding and scrap amount is reduced, and the production cost is reduced. The production cost is reduced. The method can be applied to continuous casting of high-manganese stainless steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective slag, in particular to a crystallizer protective slag for continuous casting of high manganese stainless steel and application thereof. Background Art

[0002] Manganese is a weaker austenite-forming element. As a deoxidizer, the manganese content in stainless steel is generally ≤1% or ≤2%. Studies have found that as the manganese content in stainless steel increases, the solubility of nitrogen in steel can be significantly improved. The combined addition of manganese and nitrogen is often used to replace expensive and scarce nickel in steel. In the process of developing super austenitic stainless steel and economical duplex stainless steel, adding an appropriate amount of manganese to the molten steel can not only increase the nitrogen content in the steel, stabilize or control the proportion of suitable phases, but also improve the performance of the steel, while also saving nickel to achieve the purpose of cost reduction. However, with the increase of manganese content in molten steel, especially when the manganese content reaches more than 12%, black band defects will appear on the surface of the produced steel billet during the rolling process, affecting the appearance quality and beauty, and bringing additional costs or losses to production. Among them, the main reason for the black band of this stainless steel is that the surface of the steel billet is involved in Cr-containing 2 O 3 of protective slag.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] One of the purposes of the present invention is to provide a high manganese stainless steel continuous casting mold protection slag to solve the problem of Cr-containing particles being involved in the surface of the high manganese stainless steel continuous casting billet in the prior art. 2 O 3 Technical issues of protective slag.

[0005] A second object of the present invention is to provide a high manganese stainless steel continuous casting mold protection slag for use in high manganese stainless steel continuous casting.

[0006] In a first aspect, the present invention provides a mold protection slag for continuous casting of high manganese stainless steel, wherein the protection slag comprises the following chemical components in percentage by mass: 28-38% CaO, 22-32% SiO 2 、0.5~1%Cr 2 O 3 2.2~4.5% MnO 2 , 1.5-5% MgO, 2-7% Al 2 O 3 , 3~9% Na 2 O, 4-10% F - , 3.5-6.0% C, and the balance being inevitable impurities.

[0007] Furthermore, K in the mold slag + 、Na+ and F - The sum of the mass percentages is 9 to 18%.

[0008] Furthermore, in terms of weight percentage, the raw materials of the protective slag include 40 to 70 parts of premelt, 1.5 to 7 parts of mullite powder, 4.5 to 10 parts of calcium stone powder, 0.75 to 1.5 parts of Na2CrO4, 0.5 to 6 parts of sodium feldspar powder, 3 to 6 parts of manganese carbonate, 5 to 10 parts of cryolite, 1 to 5 parts of magnesia, 3.5 to 6.0 parts of carbonaceous material and 1 to 2 parts of adhesive.

[0009] Furthermore, the carbonaceous material includes carbon black and / or graphite.

[0010] Furthermore, the adhesive includes at least one of dextrin, starch or carboxymethyl cellulose.

[0011] Furthermore, the binary basicity of the protective slag is 1.0 to 1.4.

[0012] Furthermore, the melting temperature of the mold slag is 1070-1170°C.

[0013] Furthermore, the viscosity of the mold slag at 1300° C. is 0.1-0.3 Pa·s.

[0014] In a second aspect, the present invention provides use of the mold protection slag for continuous casting of high manganese stainless steel as described in any one of the aforementioned embodiments in continuous casting of high manganese stainless steel.

[0015] Furthermore, the manganese content of the high manganese stainless steel is greater than 12%.

[0016] The invention provides a high manganese stainless steel continuous casting mold protection slag, which is pre-introduced with 0.5-1% Cr 2 O 3 This not only reduces the melting point and viscosity of the mold slag, but also helps to ensure that the mold slag absorbs Cr in the molten steel. 2 O 3 After that, the mold slag absorbs Cr 2 O 3 The concentration and physical properties of Cr in the post-treatment process did not change much; however, the study found that Cr 2 O 3 When too much is added, the viscosity gradually increases. 2 O 3 When the addition amount exceeds 2%, the mold slag deteriorates seriously; in order to ensure the stability of the properties of the mold slag, further introduce an appropriate amount of Na + and F -To reduce the melting temperature and viscosity of the mold slag, so as to promote the mold slag to absorb Mn and Cr in the molten steel to form high melting point oxides and low eutectic, ensure that the chemical balance and activity of the mold slag are relatively stable, and still have good lubrication and heat transfer effects. 2 O 3 、Na + and F - , which can make the protective slag maintain activity and stability after absorbing high melting point oxides, ensure that the stainless steel has good lubrication and heat transfer effect in the continuous casting process, effectively improve the continuous casting process, improve the quality of the ingot, reduce the black belt quality problems caused by the longitudinal cracks, edge cracks and inclusions of the continuous casting ingot, improve the product yield rate, reduce the grinding and scrapping of the ingot, and reduce the production cost. Application in high manganese stainless steel continuous casting. It can ensure that the stainless steel has good lubrication and heat transfer effect in the continuous casting process, effectively improve the continuous casting process, improve the quality of the ingot, reduce the black belt quality problems caused by the longitudinal cracks, edge cracks and inclusions of the continuous casting ingot, improve the product yield rate, reduce the grinding and scrapping of the ingot, and reduce the production cost. DETAILED DESCRIPTION

[0017] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0018] The methods and techniques of the present invention are generally performed according to conventional methods well known in the art and as described in various general and more specific references that are cited and discussed throughout the present specification unless otherwise indicated.

[0019] The inventors have found that during the casting process of high manganese stainless steel, when the molten steel is solidifying, the high alloy (alloy content ≥ 20%) in the stainless steel causes the molten steel to become sticky and the liquidus line of the molten steel to become lower. The Cr element in the molten steel is more easily oxidized, and the Cr produced after oxidation 2 O 3 It is not easy to be completely absorbed by the mold slag and float out, forming inclusions in the molten steel and being captured in the primary shell, or the mold slag absorbs Cr 2 O 3 Denatured, containing Cr 2 O 3 The protective slag is rolled into the surface of the continuous casting billet and rolled to form a black belt during steel rolling.

[0020] In one aspect, the present invention provides a mold protection slag for continuous casting of high manganese stainless steel, wherein the protection slag comprises the following chemical components in percentage by mass: 28-38% CaO, 22-32% SiO 2 、0.5~1%Cr 2 O 3 2.2~4.5% MnO 2 , 1.5-5% MgO, 2-7% Al 2 O 3 , 3~9% Na 2 O, 4-10% F - , 3.5-6.0% C, and the balance being inevitable impurities.

[0021] 0.5-1% Cr is introduced into the mold slag in advance 2 O 3 This not only reduces the melting point and viscosity of the mold slag, but also helps to ensure that the mold slag absorbs Cr in the molten steel. 2 O 3 After that, the Cr in the mold slag 2 O 3 The concentration will not change greatly, and the physical properties of the mold slag will not change much; however, the study found that Cr 2 O 3 When too much is added, the viscosity gradually increases. 2 O 3 When the addition amount exceeds 2%, the mold slag deteriorates seriously; in order to ensure the stability of the properties of the mold slag, further introduce an appropriate amount of Na + and F - To reduce the melting temperature and viscosity of the mold slag, so as to promote the mold slag to absorb Mn and Cr in the molten steel to form high melting point oxides and form a low eutectic, ensuring that the chemical balance and activity of the mold slag are relatively stable and still have good lubrication and heat transfer effects. 2 O 3 、Na + and F - , which can make the protective slag maintain activity and stability after absorbing high melting point oxides, and is conducive to the ablation of Cr 2 O 3 , making the continuous casting smooth and eliminating the defects of the casting caused by slag rolling or sticking, thereby further eliminating the black belt formed by rolling during steel rolling. Ensure that the stainless steel has good lubrication and heat transfer effect during the continuous casting process, effectively improve the continuous casting process, improve the quality of the casting, reduce the black belt quality problems caused by longitudinal cracks, edge cracks and inclusions of the continuous casting, improve the product yield, reduce the grinding and scrapping of the casting, and reduce production costs.

[0022] The mass percentage content of CaO may be, but is not limited to, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37% or 38%, and may be any value between 28 and 38%.

[0023] SiO 2 The mass percentage content can be but not limited to 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31% or 32%, and can also be any value between 22 and 32%.

[0024] Cr 2 O 3 The mass percentage content can be but not limited to 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95% or 1%, and can also be any value between 0.5 and 1%.

[0025] MnO 2 The mass percentage content can be but not limited to 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2% or 4.5%, and can also be any value between 2.2 and 4.5%.

[0026] The mass percentage content of MgO may be, but is not limited to, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, and may also be any value between 1.5 and 5%.

[0027] Al 2 O 3 The mass percentage content can be but not limited to 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5% or 7%, and can also be any value between 2 and 7%.

[0028] Na 2 The mass percentage content of O can be but is not limited to 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5% or 9%, and can also be any value between 3 and 9%.

[0029] F - The mass percentage content can be but not limited to 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, and can also be any value between 4 and 10%.

[0030] The mass percentage content of C can be but is not limited to 3.5%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8% or 6%, and can also be any value between 3.5 and 6.0%.

[0031] In some specific embodiments, K in the mold slag + 、Na + and F - The sum of the mass percentages is 9 to 18%.

[0032] Among them, Na + and F - To introduce elements, K + It is an impurity element introduced from the raw materials of the mold slag. 2 O 3 , and limit K + 、Na + and F - The sum of the mass percentages is 9-18%, which can effectively dilute and eliminate the denaturation of slag, ensure good lubrication and heat transfer effects, improve the quality of the casting and increase the product yield rate.

[0033] In some specific embodiments, the raw materials of the mold slag include, by weight percentage, 40 to 70 parts of premelt, 1.5 to 7 parts of mullite powder, 4.5 to 10 parts of calcium stone powder, 0.75 to 1.5 parts of Na 2 CrO 4 , 0.5 to 6 parts of albite powder, 3 to 6 parts of manganese carbonate, 5 to 10 parts of cryolite, 1 to 5 parts of magnesia, 3.5 to 6.0 parts of carbonaceous material and 1 to 2 parts of adhesive.

[0034] The present invention finds that when the carbonaceous material is less than 3.5 parts by weight, the heat preservation effect and the ability to control the melting rate of the protective slag are reduced, and problems such as cold steel will occur during use, which affect the smooth process and the quality of the ingot. When it is higher than 6.0 parts by weight, the protective slag produced is not suitable for granulation into balls, and the product recovery rate is low. At the same time, it is not easy to melt during use, and there is not enough liquid slag to lubricate the ingot, which can easily cause bonding accidents. Therefore, the carbonaceous material is controlled within 3.5 to 6.0 parts by weight. The addition of albite powder is conducive to the better formation of the protective slag glass, increases the surface tension of the protective slag liquid, and avoids the formation of rolled slag. Experiments have shown that without the addition of Na 2 CrO 4 The casting surface of the mold slag production site has inclusion defects and cannot meet the production needs. Therefore, Na 2 CrO 4 Adding, combined with manganese carbonate, allows the mold slag to absorb more Cr 2 O 3and MnO 2 After the impurities, the protective slag is not easy to change, there is sufficient buffer space, and MnO 2 It is also an effective substance that reduces melting point and viscosity and plays a buffering role. The above combined effect significantly reduces the black belt rate of stainless steel. In some specific embodiments, the carbonaceous material includes carbon black and / or graphite.

[0035] In some specific embodiments, the binder includes at least one of dextrin, starch or carboxymethyl cellulose.

[0036] Selecting a mold slag with a higher binary basicity can better absorb the acidic oxide impurities in the stainless steel. In some specific embodiments, the binary basicity of the mold slag is 1.0 to 1.4.

[0037] In some specific embodiments, the melting temperature of the mold slag is 1070-1170°C.

[0038] In some specific implementations, the viscosity of the mold slag at 1300° C. is 0.1-0.3 Pa·s.

[0039] According to another aspect of the present invention, there is also provided an application of the above-mentioned mold protection slag for continuous casting of high manganese stainless steel in continuous casting of high manganese stainless steel, which can ensure that the stainless steel has good lubrication and heat transfer effect during the continuous casting process, effectively improve the smoothness of continuous casting, improve the quality of the ingot, reduce the black belt quality problems caused by longitudinal cracks, edge cracks and inclusions of the continuous casting ingot, improve the product yield, reduce the grinding and scrapping of the ingot, and reduce the production cost.

[0040] Wherein, the manganese content of the high manganese stainless steel is greater than 12%.

[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] The present embodiment provides a high manganese stainless steel continuous casting mold protection slag, and its raw materials include, by weight: 6 parts by weight of albite, 9.5 parts by weight of cryolite, 1.5 parts by weight of mullite powder, 0.75 parts by weight of Na 2 CrO 4 , 3.7 parts by weight of manganese carbonate, 65.55 parts by weight of premelt, 5 parts by weight of calcium stone powder, 1 part by weight of magnesia, 1 part by weight of carbon black, 4 parts by weight of graphite, and 2 parts by weight of carboxymethyl cellulose.

[0044] Among them, the carbon content of carbon black is 98.2%, and the oil absorption value is 127g / cm 3 , iodine absorption value is 142g / kg; the carbon content of graphite is 90.2%, and the oil absorption value is 72g / cm 3 , the iodine absorption value is 82g / kg.

[0045] The mold slag contains the following chemical components by mass percentage: CaO 34.4%, SiO 2 31.2%, MgO1.61%, Cr 2 O 3 0.5%, MnO 2 2.8%, Fe 2 O 3 0.43%, Al 2 O 3 3.65%, Na 2 O8.51%, F - 6.97%, C4.62%, and the remainder are inevitable impurities.

[0046] The physical index of the mold slag is binary basicity (CaO / SiO 2 ) is 1.071, the melting temperature is 1111°C, and the viscosity at 1300°C is 0.11 Pa·s.

[0047] The protective slag was tested in a domestic factory. The test slag model was XLBX-1, the test steel grade was J1 (Mn: 18-18.3wt%), and the cross section was 200×1248mm. 2 , pulling speed 1.0~1.15m / min. A total of 3T of protective slag was tested. During the test, this type of protective slag had good spreadability and fluidity in the crystallizer, and the crystallizer liquid surface was stable. When the total slag layer was controlled at 45~65mm, the thickness of the liquid slag layer was 15~18mm, the slag layer structure was obvious, the thickness of the liquid slag layer was appropriate, the size of the crystallizer liquid surface flame was appropriate, the average slag consumption was 0.38~0.43kg / T, the slag strip generation speed in the crystallizer was slow, the surface of the ingot produced in the test was defect-free, and the detection after rolling showed no black belt defects.

[0048] Example 2

[0049] The present embodiment provides a high manganese stainless steel continuous casting mold protection slag, and its raw materials include, by weight: 3 parts by weight of albite, 9.5 parts by weight of cryolite, 6 parts by weight of mullite powder, 2 parts by weight of carbon black, 4 parts by weight of graphite, 1 part by weight of Na 2 CrO 4 , 6 parts by weight of manganese carbonate, 54.5 parts by weight of premelt, 8 parts by weight of calcium stone powder, 4 parts by weight of magnesia, and 2 parts by weight of carboxymethyl cellulose.

[0050] Among them, the carbon content of carbon black is 98.2%, and the oil absorption value is 127g / cm 3 , iodine absorption value is 142g / kg; the carbon content of graphite is 90.2%, and the oil absorption value is 72g / cm 3 , the iodine absorption value is 82g / kg.

[0051] The mold slag contains the following chemical components by mass percentage: CaO 34.94%, SiO 2 29.61%, Cr 2 O 3 0.75%, MnO 2 4.5%, MgO 3.5%, Fe 2 O 3 0.71%, Al 2 O 3 6.9%, Na 2 O 7.88%, F - 6.9%, C 5.61%, and the remainder are inevitable impurities.

[0052] The physical index of the mold slag is binary basicity (CaO / SiO 2 ) is 1.18, the melting temperature is 1143°C, and the viscosity at 1300°C is 0.13 Pa·s.

[0053] The protective slag was tested in a domestic factory. The test slag model was XLBX-2, the test steel grade was J5W (Mn: 12.3wt%), and the cross section was 180×1538mm. 2 , pulling speed 1.0~1.15m / min. A total of 5T of protective slag was tested. During the test, this type of protective slag had good spreadability and fluidity in the crystallizer, and the crystallizer liquid level was stable. When the total slag layer was controlled at 45~65mm, the thickness of the liquid slag layer was 14~18mm, the slag layer structure was obvious, the thickness of the liquid slag layer was appropriate, the size of the crystallizer liquid surface flame was appropriate, the average slag consumption was 0.4~0.451kg / T, the slag strip generation speed in the crystallizer was slow, the surface of the ingot produced in the test was defect-free, and no black belt defects were found in the test after rolling.

[0054] Example 3

[0055] The present embodiment provides a high manganese stainless steel continuous casting mold protection slag, and its raw materials include, by weight: 7 parts by weight of cryolite, 7 parts by weight of mullite powder, 3.0 parts by weight of carbon black, 3 parts by weight of graphite, 1.5 parts by weight of Na 2 CrO 4 , 5 parts by weight of manganese carbonate, 56.5 parts by weight of premelt, 10 parts by weight of calcium stone powder, 5 parts by weight of magnesia, and 2 parts by weight of dextrin.

[0056] Among them, the carbon content of carbon black is 98.2%, and the oil absorption value is 127g / cm 3 , iodine absorption value is 142g / kg; the carbon content of graphite is 90.2%, and the oil absorption value is 72g / cm 3 , the iodine absorption value is 82g / kg.

[0057] The mold slag contains the following chemical components by mass percentage: CaO 36.4%, SiO 2 28.43%, Cr 2 O 3 1.0%, MgO 4.51%, Fe 2 O 3 0.83%, MnO 2 3.67%, Al 2 O 3 3.53%, Na 2 O5.1%, F - 8.9%, C5.7%, and the remainder are inevitable impurities.

[0058] The physical index of the mold slag is binary basicity (CaO / SiO 2 ) is 1.28, the melting temperature is 1091°C, and the viscosity at 1300°C is 0.17 Pa·s.

[0059] The protective slag was tested in a domestic factory. The test slag model was XLBX-3, the test steel grade was J5L (Mn: 12.5wt%), and the cross section was 200×1248mm. 2 , pulling speed 1.0~1.15m / min. A total of 3T of protective slag was tested. During the test, this type of protective slag had good spreadability and fluidity in the crystallizer, and the crystallizer liquid level was stable. When the total slag layer was controlled at 45~65mm, the thickness of the liquid slag layer was 15~18mm, the slag layer structure was obvious, the thickness of the liquid slag layer was appropriate, the size of the crystallizer liquid surface flame was appropriate, the average slag consumption was 0.4~0.43kg / T, the slag strip generation speed in the crystallizer was slow, the surface of the ingot produced in the test was defect-free, and no black belt defects were found in the test after rolling.

[0060] Comparative Example 1

[0061] The present comparative example provides a continuous casting crystallizer protection slag for high manganese stainless steel. The raw materials thereof include, by weight: 8 parts by weight of cryolite, 8 parts by weight of mullite powder, 3 parts by weight of carbon black, 5 parts by weight of graphite, 59 parts by weight of premelt, 11 parts by weight of calcium stone powder, 3 parts by weight of magnesia, and 2 parts by weight of carboxymethyl cellulose.

[0062] Among them, the carbon content of carbon black is 98.2%, and the oil absorption value is 127g / cm3 , iodine absorption value is 142g / kg; the carbon content of graphite is 90.2%, and the oil absorption value is 72g / cm 3 , the iodine absorption value is 82g / kg.

[0063] The mold slag contains the following chemical components by mass percentage: CaO 33.31%, SiO 2 32.17%, MgO2.48%, Fe 2 O 3 0.79%、Al 2 O 3 7.3%, Na 2 O 6.73%, F - 7.09%, C 7.53%, and the balance are inevitable impurities.

[0064] The physical index of the mold slag is binary basicity (CaO / SiO 2 ) is 1.04, the melting temperature is 1175°C, and the viscosity at 1300°C is 0.20 Pa·s.

[0065] The protective slag was tested in a domestic factory. The test slag model was XLBX-4, the test steel grade was J1 (Mn: 18-18.3 wt%), and the cross section was 180×1546 mm. 2 , pulling speed 1.0~1.05m / min. A total of 2T of protective slag was tested. During the test, this type of protective slag had good spreadability and fluidity in the crystallizer when used in the first two furnaces, and the crystallizer liquid level was stable. When the total slag layer was controlled at 45~65mm, the liquid slag layer thickness was 5~9mm, the slag layer structure was obvious, the liquid slag layer thickness was thin, the size of the crystallizer liquid surface flame was appropriate, the average slag consumption was 0.34~0.38kg / T, and the slag strips in the crystallizer were generated slowly. As the test time increased, by the fifth furnace, the consumption gradually decreased, the liquid slag layer thickened, the slag strips gradually grew, and the protective slag showed signs of degeneration. In the second half of the test process, there were 2 bonding alarms, and there were no bonding marks and scarring on the surface of the produced ingot. The pickling black belt rate of the rolled product was 23.8%, and the downgrade rate was 5.3%, which could not meet the production needs.

[0066] Comparative Example 2

[0067] This comparative example is based on Example 1 and removes Na 2 CrO 4 , calculated by weight, the raw materials include: 6 parts by weight of albite, 9.5 parts by weight of cryolite, 0.5 parts by weight of mullite powder, 3.7 parts by weight of manganese carbonate, 67.3 parts by weight of premelt, 5 parts by weight of calcium stone powder, 1 part by weight of magnesia, 1 part by weight of carbon black, 4 parts by weight of graphite, and 2 parts by weight of carboxymethyl cellulose.

[0068] Among them, the carbon content of carbon black is 98.2%, and the oil absorption value is 127g / cm 3 , iodine absorption value is 142g / kg; the carbon content of graphite is 90.2%, and the oil absorption value is 72g / cm 3 , the iodine absorption value is 82g / kg.

[0069] The mold slag contains the following chemical components by mass percentage: CaO 34.92%, SiO 2 32.6%, MgO1.471%, Fe 2 O 3 0.43%, Al 2 O 3 3.65%, MnO 2 2.8%, Na 2 O 9.51%, F - 6.97%, C 4.62%, and the remainder are inevitable impurities.

[0070] The physical index of the mold slag is binary basicity (CaO / SiO 2 ) is 1.071, the melting temperature is 1163°C, and the viscosity at 1300°C is 0.17 Pa·s.

[0071] The protective slag was tested in a domestic factory. The test slag model was XLBX-5, the test steel grade was J5L (Mn: 12.5wt%), and the cross section was 180×1546mm. 2 , pulling speed 1.0-1.1m / min. A total of 1T of protective slag was tested. During the test, this type of protective slag had good spreadability and fluidity in the crystallizer, and the liquid level of the crystallizer was stable. When the total slag layer was controlled at 45-65mm, the thickness of the liquid slag layer was 6-10mm, the slag layer structure was obvious, the thickness of the liquid slag layer changed rapidly, and the average slag consumption was 0.36-0.39kg / T. There were many slag rolling phenomena. The surface of the ingot produced in the test had inclusion defects, and the degradation rate was 4.1%, which could not meet the production needs.

[0072] Comparative Example 3

[0073] The present comparative example provides a high manganese stainless steel continuous casting mold protection slag, which comprises, by weight, 3 parts of albite, 9.5 parts of cryolite, 6 parts of mullite powder, 2.0 parts of carbon black, 4 parts of graphite, 5 parts of Na 2 CrO 4 , 6 parts by weight of manganese carbonate, 54.5 parts by weight of premelt, 8 parts by weight of calcium stone powder, 4 parts by weight of magnesia, and 2 parts by weight of carboxymethyl cellulose.

[0074] Among them, the carbon content of carbon black is 98.2%, and the oil absorption value is 127g / cm3 , iodine absorption value is 142g / kg; the carbon content of graphite is 90.2%, and the oil absorption value is 72g / cm 3 , the iodine absorption value is 82g / kg.

[0075] The mold slag contains the following chemical components by mass percentage: CaO 34.94%, SiO 2 29.61%, Cr 2 O 3 3.36%, MnO 2 4.5%, MgO 3.5%, Fe 2 O 30.71%, Al 2 O 3 6.9%, Na 2 O7.88%, F - 5.9%, C 5.61%, and the remainder are inevitable impurities.

[0076] The physical index of the mold slag is binary basicity (CaO / SiO 2 ) is 1.18, the melting temperature is 1189°C, and the viscosity at 1300°C is 0.25 Pa·s.

[0077] The protective slag was tested in a domestic factory. The test slag model was XLBX-6, the test steel grade was J5L (Mn: 12.5wt%), and the cross section was 180×1546mm. 2 , pulling speed 1.0~1.1m / min. A total of 1T of test protection slag was produced. During the test, the melting speed of this type of protection slag in the crystallizer was slow, the liquid slag layer was 5~7mm, which was obviously too thin, and the adhesion alarm was too frequent. The protection slag was forced to be replaced before it was fully used, and the test was stopped.

[0078] In summary, the protective slag provided in this application is suitable for continuous casting of high manganese stainless steel with a manganese content exceeding 12%. Its design principle is unique and feasible, the selection of raw materials and the design of performance indicators are reasonable, the lubrication and heat transfer effects are good, and the thickness of the liquid slag layer is uniform and moderate, which can ensure the smooth continuous casting process of high manganese stainless steel and prevent the formation of black belts.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A mold protection slag for high manganese stainless steel continuous casting, It is characterized in that The mold slag includes the following chemical components in percentage by mass: 28-38% CaO, 22-32% SiO 2 、0.5~1%Cr 2 O 3 2.2~4.5% MnO 2 , 1.5-5% MgO, 2-7% Al 2 O 3 , 3~9% Na 2 O, 4-10% F - , 3.5-6.0% C, and the balance being inevitable impurities.

2. The mold protection slag for continuous casting of high manganese stainless steel according to claim 1, It is characterized in that The K in the mold slag + 、Na + and F - The sum of the mass percentages is 9 to 18%.

3. The mold protection slag for continuous casting of high manganese stainless steel according to claim 2, It is characterized in that The raw materials of the protective slag include 40 to 70 parts of premelt, 1.5 to 7 parts of mullite powder, 4.5 to 10 parts of calcium stone powder, 0.75 to 1.5 parts of Na 2 CrO 4 , 0.5 to 6 parts of albite powder, 3 to 6 parts of manganese carbonate, 5 to 10 parts of cryolite, 1 to 5 parts of magnesia, 3.5 to 6.0 parts of carbonaceous material and 1 to 2 parts of adhesive.

4. The mold protection slag for continuous casting of high manganese stainless steel according to claim 3, It is characterized in that The carbonaceous material includes carbon black and / or graphite.

5. The mold protection slag for continuous casting of high manganese stainless steel according to claim 3, It is characterized in that The binder includes at least one of dextrin, starch or carboxymethyl cellulose.

6. The mold protection slag for continuous casting of high manganese stainless steel according to any one of claims 1 to 5, It is characterized in that The binary basicity of the protective slag is 1.0-1.

4.

7. The mold protection slag for continuous casting of high manganese stainless steel according to claim 6, It is characterized in that The melting temperature of the protective slag is 1070-1170°C.

8. The mold protection slag for continuous casting of high manganese stainless steel according to claim 7, It is characterized in that The viscosity of the protective slag at 1300° C. is 0.1-0.3 Pa·s.

9. Use of the mold protection slag for continuous casting of high manganese stainless steel according to any one of claims 1 to 8 in continuous casting of high manganese stainless steel.

10. The use according to claim 9, It is characterized in that The manganese content of the high manganese stainless steel is greater than 12%.